Pengaruh Return On Equity Dan Current Ratio Terhadap Harga Saham Pada Perusahaan Sub Sektor Makanan Dan Minuman Yang Terdaftar Di Bursa Efek Indonesia Tahun 2017-2019 - Miftachul Jannah; Budi Wahono; Khalikussabir Khalikussabir (E-JRM : Elektronik Jurnal Riset Manajemen, 2021)
AbstractThe stock price is a very important factor and must be considered by investors in investing because the stock price shows the value and achievements of a company. This study has the objectives: 1) Return On Equity and Current Ratio Simultaneously to Stock Prices, 2) Return On Equity and Current Ratio Partially Against Stock Prices. This research method is quantitative. This population is food and beverage companies listed on the Indonesia Stock Exchange for the 2017-2019 study period. The method of determining the sample by using purposive sampling method with several predetermined criteria, the sample size is 17 companies. The research data is secondary data obtained from the Indonesian Capital Market Directory (ICMD) and Financial Reports (Annual Report) for the 2017-2019 period. Answering research problems and testing research hypotheses used panel data analysis techniques, with SPSS version 25 application tools.The results of this study indicate that the simultaneous calculation of the hypothesis between the ROE and CR variables has a significant effect on stock prices with a significant value of 0.000 <0.05. While the partial calculation of the hypothesis, namely ROE, there is a significant effect on stock prices, indicated by a significance level of 0.000 <0.05, and CR has no significant effect on stock prices with a significant level of 0.665> 0.05. Keywords: Return On Equity (ROE), Current Ratio (CR), and Stock Price.